The 6-min Walk Test Reflects Functional Capacity in Primary Care and Obese Patients - Baillot, A.; Baillargeon, J.-P.; Brown, C.; Poder, T.; Langlois, M.-F. (International Journal of Sports Medicine, 2015)
The main purpose of this study was to determine the association between the 6-min walk test distance (6MWTD) and physical functional capacity (PF) in primary care patients, as well as in obese individuals. We studied 351 subjects (age=56.8±14.6 years; BMI=29.4±5.7 kg/m2; 68% women), including 141 obese subjects (BMI≥30 kg/m2), recruited in 10 different family practices. Physical (PCS) and mental component summary of the health-related quality of life (HRQOL) and the 8 sub-scores were measured using the Short Form-36 Health Survey. Anthropometry, vital signs and physical testing were measured according to standardized protocols. Recreational physical activity (LPA) and sedentary levels were determined using the Canadian Community Health Survey. In a stepwise multivariate analysis, 65% of the 6MWTD variance was explained by PF of the HRQOL, age, quadriceps strength, number of chronic diseases, LPA categories, BMI, resting heart rate, PCS, height and TV-viewing categories in primary care subjects. In the obese individuals, PF, age, quadriceps strength and BMI explained 57% of the 6MWTD variance. In these 2 groups, 44% of the 6MWTD variance is explained by PF only. To conclude, the 6MWTD is strongly associated with PF of the HRQOL. Thus, it adequately reflects physical limitations in daily life activities of primary care patients, including obese individuals.
Keywords: physical fitness; quality of life; primary care; obesity